2016
DOI: 10.1177/0734282916669231
|View full text |Cite
|
Sign up to set email alerts
|

Biological Gender Differences in Students’ Errors on Mathematics Achievement Tests

Abstract: This study investigated developmental gender differences in mathematics achievement, using the child and adolescent portion (ages 6-19 years) of the Kaufman Test of Educational Achievement-Third Edition (KTEA-3). Participants were divided into two age categories: 6 to 11 and 12 to 19. Error categories within the Math Concepts & Applications and Math Computation subtests of the KTEA-3 were factor analyzed and revealed five error factors. Multiple ANOVA of the error factor scores showed that, across both age cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This shows the fact that the average statistical thinking ability of students is not influenced by the gender factors of the students themselves. This is consistent with the research fact that gender does not have an influence on students' cognitive improvement both in learning achievement and student motivation in learning [44]- [48].…”
Section: Implementation Phasesupporting
confidence: 92%
“…This shows the fact that the average statistical thinking ability of students is not influenced by the gender factors of the students themselves. This is consistent with the research fact that gender does not have an influence on students' cognitive improvement both in learning achievement and student motivation in learning [44]- [48].…”
Section: Implementation Phasesupporting
confidence: 92%
“…According to the 2019 Nation’s Report Card, there was only a small three-point difference between male and female students in fourth grade (NCES, 2020), although McCormick and O’Connor (2015) found girls with more conflictual STR exhibited lower math achievement compared to boys with similar levels of conflictual relationships. Stewart et al (2017) also found statistically significant gender differences for math problems that required multiple steps to solve, with males outperforming females.…”
Section: Importance Of Math Achievement In Early Gradesmentioning
confidence: 87%
“…Following this train of thought, gender differences in mathematical and science Olympiads should be similar to gender differences found in the group of top performing students in mathematics and science education. For the top science performers, strikingly low female rates were reported among 12‐ to 19‐year‐old students in the United States and several other countries (Dimitrov, ; Fan, Chen, & Matsumoto, ; OECD, ; Reilly et al, ; Stewart et al, ). In Finland and Latvia on the other hand, no significant gender differences were found in science achievement among 15‐year‐old students in the 90th percentile group (OECD, ).…”
Section: Discussionmentioning
confidence: 99%